Epidemiology of community-acquired and recurrent Clostridioides difficile infection. (May 2021) - Fu, Yichun; Luo, Yuying; Grinspan, Ari M
Clostridioides difficile infection is a leading cause of healthcare-associated infections with significant morbidity and mortality. For the past decade, the bulk of infection prevention and epidemiologic surveillance efforts have been directed toward mitigating hospital-acquired C. difficile . However, the incidence of community-associated infection is on the rise. Patients with community-associated C. difficile tend to be younger and have lower mortality rate. Rates of recurrent C. difficile infection overall have decreased in the United States, but future research and public health endeavors are needed to standardize and improve disease detection, stratify risk factors in large-scale population studies, and to identify regional and local variations in strain types, reservoirs and transmission routes to help characterize and combat the changing epidemiology of C. difficile .